Assimilation of gelatin-acacia microencapsulated lipid by Pacific oyster (Crassostrea gigas) spat - Knauer, J; Southgate, Paul C (Aquaculture, 1997)
Gelatin-acacia microcapsules (GAM) are commonly used as a delivery vehicle for lipids in nutritional studies with bivalves. In this study the efficiency with which lipid contained in GAM was assimilated by Pacific oyster (Crassostrea gigas) spat was determined. The marine diatom Chaetoceros muelleri was cultured in the presence of 14C-sodium bicarbonate for 24 h. The 14C-lipid fraction was extracted, mixed with corn oil and microencapsulated in GAM. Spat assimilated 14C-lipids from a mixed diet of the marine flagellate Dunaliella tertiolecta (80%) and GAM (20%) with an efficiency of 79.9 ± 2.9%, while spat fed a 100% GAM diet assimilated 14C-lipids at a rate of 57.1 ± 5.2%. Addition of 100 mg l-1 of the antibiotic Thimerosal to both a mixed diet and GAM only significantly reduced bacterial degradation of GAM over 24 h. The high assimilation efficiencies underline the potential of GAM as carrier of lipids in nutritional studies with bivalves.